Business analysis & valuation: Using financial statements - Palepu, Krishna G.; Healy, Paul M. (New Delhi Cengage Learning India Pvt. Ltd., 2013)
Business Analysis and Valuation gives you a practical, in-depth approach to the subject of accounting valuation. It includes a significant number of case studies exploring various issues in this field, as well as a new case feature at the end of each chapter. New 'Industry insights' boxes show you how the content translates to the workplace.